Cyclic Performance of Welded Unreinforced Flange-Welded Web Moment Connections. Issue 4 (November 2014) - Han, Sang Whan; Moon, Ki Hoon; Jung, Jin
The welded unreinforced flange-welded web (WUF-W) moment connection is a prequalified connection for the special moment frame (SMF) specified in AISC 358-10. In this study, inelastic cyclic tests of four WUF-W specimens were conducted to evaluate the seismic performance of WUF-W connections with different beam depths and panel zone strength ratios. The specimens were made to satisfy the design and detailing criteria specified in AISC 341-10 and AISC 358-10. Test results showed that the WUF-W connections with a beam depth of 692 mm passed the acceptance criteria required for SMF connections, whereas the WUF-W connections with a beam depth of 890 mm did not meet the criteria.